Comparative Study of Latanoprost Drug Delivery Systems for Glaucoma Treatment and Their Interaction with the Tear Film Lipid Layer Models - Saija, Maria Chiara; Vazdar, Katarina; Pajerski, Wojciech; Olżyńska, Agnieszka; Daull, Philippe; Garrigue, Jean-Sebastien; Cwiklik, Lukasz (Molecular pharmaceutics, 2024)
This study investigates the interaction of two approved and one newly developed latanoprost formulation with in vitro and in silico models of the tear film and tear film lipid layer (TFLL). Latanoprost, a prostaglandin analogue used for intraocular elevated pressure treatment, is topically delivered by nanocarriers within aqueous solutions or emulsions. The study focuses on the impact of these carriers on drug interactions with the tear film and their effect on the TFLL. Three different types of latanoprost carriers, micellar, nanoemulsion, and polymer-based, were compared, and each revealed distinct interaction patterns with the TFLL. Surface pressure kinetics demonstrated a rapid increase for the benzalkonium chloride formulation and a slow rise for the preservative-free variants. Visualization of the acellular in vitro TFLL model revealed different patterns of incorporation for each formulation, indicating unique interaction mechanisms. Molecular dynamics simulations further revealed different mechanisms of drug release in the TFLL between micellar and nanoemulsion formulations. In-depth examination highlighted the role of triglyceride molecules in replenishing the nonpolar layer of the TFLL, which suggests potential improvements in ocular surface compatibility by adjusting the quality and concentration of the oily phase. These findings suggest the potential for optimizing latanoprost formulations by tuning the oily phase-to-surfactant ratio and selecting suitable surfactants.
Keywords: Glaucoma; Antihypertensive Agents; Latanoprost; lidé; Intraocular Pressure; oči; glaukom; nitrooční tlak; antihypertenziva; Eye; latanoprost; Humans; Drug Delivery Systems; lékové transportní systémy